Study of the biaxial fatigue behaviour and overloads on S355 low carbon steel - Sánchez-Cruces, Manuel Alejandro; Mokhtarishirazabad, Mehdi; Moreno-Morales, María Belén; Zanganeh, M; López-Crespo, Pablo (Elsevier, 2020)
This work aimed to study the fatigue behaviour of S355 low carbon steel under uniaxial and biaxial loading conditions and to measure the overload effects under both types of loads. The analysis is performed with a local strain approach and with damage tolerance approach. Local strain based investigation was based on Fatemi Socie critical plane model. This allows the life reduction caused by growing the crack from a stress raiser to be quantified. The fatigue life reduction caused by applying simultaneously torsional and tension loads was also evaluated with Fatemi-Socie model. In addition, the crack opening displacement (COD) and the effective stress intensity factor (SIF) were evaluated experimentally via full-field technique of digital image correlation (DIC). Both COD and SIF have been useful to understand the transient effects caused by a 40% overload under the two types of load. In addition, COD measurements allowed the offset compliance method for evaluating the opening load to be applied on a cylindrical specimen subjected to tension load. SIF estimation was also useful to quantify the mode mixity (I + II) developed during the experiment under the two types of load.
Keywords: Materiales - Fatiga; Biaxial fatigue; Overload; Critical plane methods; COD; Effective stress intensity factor